Regression Analysis of Ground Water Quality Data of Aurangabad Near Kham River (Maharashtra) - Ubale, M.B.; Farooqui, Mazahar; Md. Arif, Pathan; Zaheer, Ahmed; Dhule, D.G. (Asian Journal of Chemistry, 2010)
Ground water samples of bore-well from nearby area of Kham river, Aurangabad (Maharashtra) have been analyzed for various water quality constituents during the year 1998 and correlation coefficients among different parameters were determined. A regression equation to predict the concentration of water quality constituents having significant correlation coefficient with conductivity and the usefulness of this equation in predicting the ground water quality are discussed in the paper.